Lifetime management for aortic stenosis: Planning for future therapies. Issue 3 (September 2022) - Basman, Craig; Pirelli, Luigi; Singh, Varinder P; Reimers, Carl D; Hemli, Jonathan; Brinster, Derek R; Patel, Nirav C; Scheinerman, S Jacob; Kliger, Chad A
Highlights: Among patients that undergo transcatheter aortic valve replacement (TAVR), options for valve failure include TAVR explant with surgical aortic valve replacement (SAVR) or TAV-in-TAV In younger patients that elect to undergo SAVR, options for bioprosthetic failure are TAV-in-SAV or redo SAVR. This review discusses how options for future therapies affects the decision of SAVR vs TAVR in younger patients Summary: A shift to lifetime management has gained more focus with the approval of low-risk transcatheter aortic valve replacement (TAVR). This paper is therefore focused on the different approaches for lifetime management. Herein we discuss the procedural safety, durability, performance, and future options for each lifetime management strategy. In younger patients that elect to undergo surgical aortic valve replacement (SAVR), options for bioprosthetic failure are TAV-in-SAV or redo SAVR. Among patients that undergo TAVR, options for valve failure include TAVR explant with SAVR or TAV-in-TAV. Additionally, there are patients who may require a third valvular intervention. The initial therapy may limit re-intervention options down the road. This review discusses how options for future therapies affect the decision of SAVR vs TAVR in younger patients. Graphical abstract: Image, graphical abstract